High efficacy of direct‐acting anti‐viral agents in hepatitis C virus‐infected cirrhotic patients with successfully treated hepatocellular carcinoma. Issue 12 (3rd May 2018) - Persico, M.; Aglitti, A.; Aghemo, A.; Rendina, M.; Lleo, A.; Ciancio, A.; Di Marco, V.; Lampertico, P.; Brunetto, M. R.; Zuin, M.; Andreone, P.; Villa, E.; et al.
Summary: Background: The efficacy of direct‐acting anti‐viral (DAA) therapy in patients with a history of hepatocellular carcinoma (HCC) is unknown. Aim: We prospectively evaluated whether previously treated HCC affects DAA efficacy in a large real‐life cohort of cirrhotic patients. Methods: From January to December 2015 all consecutive HCV mono‐infected patients with cirrhosis and/or history of HCC attending 10 Italian tertiary liver centres were enrolled. Baseline characteristics and response to therapy were recorded. 1927 patients were enrolled (mean age: 62.1 ± 10.9 years; 1.205 males). Genotype 1 was the most frequent (67.9%) followed by genotypes 3 (12.4%), 2 (11.2%) and 4 (8.6%). 88.4% and 10.9% of cases were classified Child A and B, respectively, and 14 (<1%) cases were classified Child C. Ascites and hepatic encephalopathy occurred in 10.7% and 3.2% of patients, respectively. Varices were detected in 39.3% of patients. Suboptimal and optimal treatment was prescribed: 15.9% of patients received sofosbuvir/simeprevir, 33.4% sofosbuvir/ledipasvir, 20.2% a Viekirax + Exviera regimen, 15.7% sofosbuvir/ribavirin, 9.9% sofosbuvir/daclatasvir and 3.4% Viekirax; 1.3% of patients received an interferon‐based regimen. Results: The sustained virologic response (SVR) rate at intention‐to‐treat analysis was 95.1%. It differed significantly across Child classes, that is, 96.3%, 86.1% and 71.4% Child A, B and C, respectively ( P  < 0.0001) and across genotypes ( P  = 0.002). The SVR rate did not differ between patients with (95.0%) and those without previous HCC (95.1%). At multivariable analysis, SVR was significantly associated with HCV genotype, Child class. Conclusion: This large real‐life study proves that the efficacy of DAA in cirrhotic patients is not impaired by successfully treated HCC.